Stability and reproducibility of semi-quantitative risk assessment methods within the occupational health and safety scope - Carvalho, F; Melo, R B (Work (Reading, Mass.), 2015)
In many enterprises the semi-quantitative approach turns out to be the available and most suitable technique to perform a risk assessment. Despite its advantages, we cannot disregard the existing gap in terms of validation of this type of applications. This paper reports a study about risk assessments' reliability, namely both inter-coder (reproducibility) and intra-coder (stability) reliability of the semi-quantitative approach. This study comprised 4 fundamental stages. Data collection relied on free and systematized observations and made use of video recording, documental research, analysis grids and questionnaires specifically developed for this purpose. A set of different analysts were asked to use four semi-quantitative risk assessment methods (in two different moments) to estimate and assess six risks identified in two tasks accomplished to produce Airbags. The Krippendorff's Alpha Coefficient (α K) was the agreement measure selected to evaluate both inter-coder and intra-coder consensus. The preliminary results revealed a general low concordance (α K < 0.6) for both reliability evaluations. Apparently there are no relevant differences between the risk assessment results obtained by individuals with different levels of experience or expertise. This study revealed that the use of the semi-quantitative approach should be done with caution.